Synthesis and application of [Zr-UiO-66-PDC-SO3H]Cl MOFs to the preparation of dicyanomethylene pyridines via chemical and electrochemical methods - Amir Mohammad Naseri (Nature Portfolio, 2021)
Abstract A metal–organic framework (MOF) with sulfonic acid tags as a novel mesoporous catalyst was synthesized. The precursor of Zr-UiO-66-PDC was synthesized both via chemical and electrochemical methods. Then, zirconium-based mesoporous metal–organic framework [Zr-UiO-66-PDC-SO3H]Cl was prepared by reaction of Zr-UiO-66-PDC and SO3HCl. The structure of [Zr-UiO-66-PDC-SO3H]Cl was confirmed by FT-IR, PXRD, FE-SEM, TEM, BET, EDX, and Mapping analysis. This mesoporous [Zr-UiO-66-PDC-SO3H]Cl was successfully applied for the synthesis of dicyanomethylene pyridine derivatives via condensation of various aldehyde, 2-aminoprop-1-ene-1,1,3-tricarbonitrile and malononitrile. At the electrochemical section, a green electrochemical method has successfully employed for rapid synthesis of the zirconium-based mesoporous metal–organic framework UiO-66-PDC at room temperature and atmospheric pressure. The synthesized UiO-66-PDC has a uniform cauliflower-like structure with a 13.5 nm mean pore diameter and 1081.6 m2 g−1 surface area. The described catalyst [Zr-UiO-66-PDC-SO3H]Cl was also employed for the convergent paired electrochemical synthesis of dihydropyridine derivatives as an environmentally friendly technique under constant current at 1.0 mA cm−2 in an undivided cell. The proposed method proceeds with moderate to good yields for the model via a cooperative vinylogous anomeric based oxidation.